Gap-coupled Frequency Agile Active Microstrip Antenna - Gautam A.K.; Vishvakarma B.R. (My University, 2025)
Gap-coupled frequency agile active microstrip antenna is proposed, in which the operating frequency of the rectangular microstrip antenna is electronically controllable with the bias voltage of the MOS capacitor. Effect of the parasitic element is studied with gap-coupling. Theoretical investigations based on modal cavity model are carried out for the gap-coupled frequency agile active microstrip antenna. It is found that the antenna shows wide tunability (1.43 GHz) that depends inversely on gap length. © 2006 Institute of Electrical and Electronics Engineers Inc.. All rights reserved.